Repetition of Epizeuksis in the Poetry Collection the Road to Your Home The Work of Acep Zamzam Noor - Armet, Armet (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
This research is motivated by the fact that poetry is one of the most popular forms of literary works presented in beautiful and imaginative language. Even poetry is considered as a series of words that describe the feelings of the author. Furthermore, the frequent use of repetition in poetry written by poets. This type of research is qualitative research. The method used in this research is descriptive analysis method. The data collection technique used in this study uses the listening method with note taking techniques. The results of the study found a form of epizeuksis repetition in the poetry collection Jalan To Rumahmu which can be seen in various poetry titles including “Di Sini”, “Lagu Fajar”, “Corso Garibaldi 138, “Senza Titolo”, “Disebuah Basilica, Assisi”, “Di Negeri Air”,“Menanti Kelahiran”, “Cerita Buat Imana Tahira”, “Montmarte”, and “Buat Malika Hamoudi”.